PENERAPAN MODEL QUANTUM TEACHING DALAM PEMBELAJARAN MENYIMAK CERITA PENDEK - rita arianti; Herwandi H (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2018)
Abstract: Purpose of this research is to improve the activity and student learning outcomes in the study listened to a short story by applying the model of quantum in Class XI IPS 1 SMA 2 Rambah Hilir. The results showed the application of quantum learning model of listening to short stories can increase the activity and student learning outcomes in class XI IPS 1 SMA 2 Rambah Rokan Hilir Riau Hulu. The results are as follows: 1) Improving the quality of student activity from the first cycle of 46%, the second cycle of 62%, the third cycle of 76%, and cycle IV by 96%, an increase in the activity of students in the study listened to a short story to be very qualified, 2) thoroughness of learning outcomes of the first cycle of 41.38%, the second cycle of 55.17%, 72.41% for the third cycle, and fourth cycle of 100%, an increase excellent learning outcomes, 3) average value of the first cycle of 73.06, the second cycle of 78.65, 82.07 for the third cycle, and fourth cycle of 87.10. Could be concluded in the classical model of quantum teaching can increase the average value of listening to a short story class XI IPS 1 SMA Negeri 2 Rambah Hilir.Abstrak: Tujuan penelitian ini adalah untuk meningkatkan aktivitas dan hasil belajar siswa pada pembelajaran menyimak cerita pendek dengan menerapkan model quantum teaching di Kelas XI IPS 1 SMA Negeri 2 Rambah Hilir. Hasil penelitian ini menunjukkan penerapan model quantum teaching dalam pembelajaran menyimak cerita pendek dapat meningkatkan aktivitas dan hasil belajar siswa kelas XI IPS 1 SMA Negeri 2 Rambah Hilir Kabupaten Rokan Hulu-Riau.. Hasilnya sebagai berikut: 1) Peningkatan kualitas aktivitas siswa dari siklus I sebesar 46 %, siklus II sebesar 62 %, siklus III sebesar 76 %, dan siklus IV sebesar 96%, terjadi peningkatan aktivitas siswa pada pembelajaran menyimak cerpen menjadi sangat berkualitas, 2) Ketuntasan hasil belajar dari siklus I sebesar 41,38 %, siklus II sebesar 55,17%, siklus III sebesar 72,41%, dan siklus IV sebesar 100%, terjadi peningkatan hasil belajar yang sangat baik, 3) Rata-rata nilai dari siklus I sebesar 73,06, siklus II sebesar 78,65, siklus III sebesar 82,07, dan siklus IV sebesar 87,10. Dapat disimpulkan secara klasikal bahwa model quantum teaching dapat meningkatkan rata-rata nilai menyimak cerita pendek siswa kelas XI IPS 1 SMA Negeri 2 Rambah Hilir.